Circ_0003945: an emerging biomarker and therapeutic target for human diseases - Zhang, Xiaofei; Ma, Li; Wan, Li; Wang, Haoran; Wang, Zhaoxia (Frontiers in Oncology, 2024)
Due to the rapid development of RNA sequencing techniques, a circular noncoding RNA (ncRNA) known as circular RNAs (circRNAs) has gradually come Into focus. As a distinguished member of the circRNA family, circ_0003945 has garnered attention for its aberrant expression and biochemical functions in human diseases. Subsequent studies have revealed that circ_0003945 could regulate tumor cells proliferation, migration, invasion, apoptosis, autophagy, angiogenesis, drug-resistance, and radio-resistance through the molecular mechanism of competitive endogenous RNA (ceRNA) during tumorigenesis. The expression of circ_0003945 is frequently associated with some clinical parameters and implies a poorer prognosis in the majority of cancers. In non-malignant conditions, circ_0003945 also holds considerable importance in diseases pathogenesis. This review aims to recapitulate molecular mechanism of circ_0003945 and elucidates its potential as a diagnostic and therapeutic target in neoplasms and other diseases.